Tópicos Em Ciências Da Saúde-Volume 11 2019
DOI: 10.36229/978-85-7042-157-9.cap.14
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de disfunção sexual em sobreviventes de câncer de mama

Abstract: Capítulo 3: Análise dos efeitos da cinesioterapia, laserterapia e eletroterapia no tratamento pós-cirúrgico de fratura da cabeça do rádio proximal no idoso: Um estudo de caso.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…During pregnancy, hormonal changes, particularly those involving estrogen and progesterone, promote alterations in the oral cavity. These changes encompass vascular, microbiological, and cellular modifications, and they create a favorable environment for the initiation and development of various pathologies [15][16][17][18]. In 2017, Silva de Araujo reported that changes that occur in the microcirculatory system during pregnancy involve swelling of endothelial cells, increased adhesion of platelets and leukocytes to vessel walls, formation of microthrombi, alteration in perivascular mast cells, increased vascular permeability, and vascular proliferation [15].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…During pregnancy, hormonal changes, particularly those involving estrogen and progesterone, promote alterations in the oral cavity. These changes encompass vascular, microbiological, and cellular modifications, and they create a favorable environment for the initiation and development of various pathologies [15][16][17][18]. In 2017, Silva de Araujo reported that changes that occur in the microcirculatory system during pregnancy involve swelling of endothelial cells, increased adhesion of platelets and leukocytes to vessel walls, formation of microthrombi, alteration in perivascular mast cells, increased vascular permeability, and vascular proliferation [15].…”
Section: Discussionmentioning
confidence: 99%
“…These changes encompass vascular, microbiological, and cellular modifications, and they create a favorable environment for the initiation and development of various pathologies [15][16][17][18]. In 2017, Silva de Araujo reported that changes that occur in the microcirculatory system during pregnancy involve swelling of endothelial cells, increased adhesion of platelets and leukocytes to vessel walls, formation of microthrombi, alteration in perivascular mast cells, increased vascular permeability, and vascular proliferation [15]. Estrogen and progesterone, in association with inflammatory mediators, may induce changes in vascular responses and turnover of connective tissue in the periodontium, leading to higher prevalence of inflammatory processes during periods of hormonal fluctuation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Segundo Araújo et al 18 , as mulheres que apresentam DSF podem ter depressão moderada ou grave, sendo 13,5 vezes maior do que nas mulheres que não possui DSF. Porém como em nosso estudo a amostra de mulheres que utilizam antidepressivos foi baixa, sendo de somente 8 mulheres, assim torna-se necessário estudos futuros e especificamente voltados a essa temática para um levantamento de dados com maior precisão e confiabilidade.…”
Section: Tabela 2 Análise Da Correlação Linear Das Fases Da Resposta Sexual Feminina Em Seus Diferentes Domínios De Mulheres Após Mastectunclassified